Reviewing Co-creation Method in the Context of Visual Arts Co-creation: A Case Study of Usungan Parade Project - Mat, Mohamad Faizuan; Saidon, Hasnul Jamal; Khiri, Muhammad Jazlan Ahmad; Leong, Sarah Naemah Aman; Al-Nahari, Nourah Nasser (Journal of Visual Art and Design, 2024)
In this paper, co-creation through visual art as a form of community engagement is explored and discussed through its definition, origin, method, practice, context, and potential. The Usungan Parade co-creation project at a khatam al-Quran event in Kabong, Sarawak, East Malaysia served as a case study through a qualitative analysis to explore the experiences and interpretations of the community related to the co-creation phenomenon. The study was conducted through participant observation and interviews with a sample drawn from heads of families, usungan craftsmen, and audience members. Six factors were identified in this community engagement project using the co-creation model. Then we elaborated how the participants interpreted the value of co-creation obtained from their activities. The objective was to build a strong argument for an in-depth study of implementing co-creation in a particular community. This research found that co-creation can contribute to reducing the gaps between those who can produce art and society, especially through the participation of ‘non-art affiliated’ communities and artistic excellence.